Micro-/Nano-Scales Direct Cell Behavior on Biomaterial Surfaces - Wang, Shuo (Molecules, 2018)
Cells are the smallest living units of a human body’s structure and function, and their behaviors should not be ignored in human physiological and pathological metabolic activities. Each cell has a different scale, and presents distinct responses to specific scales: Vascular endothelial cells may obtain a normal function when regulated by the 25 µm strips, but de-function if the scale is removed; stem cells can rapidly proliferate on the 30 nm scales nanotubes surface, but stop proliferating when the scale is changed to 100 nm. Therefore, micro and nano scales play a crucial role in directing cell behaviors on biomaterials surface. In recent years, a series of biomaterials surface with micro and/or nano scales, such as micro-patterns, nanotubes and nanoparticles, have been developed to control the target cell behavior, and further enhance the surface biocompatibility. This contribution will introduce the related research, and review the advances in the micro/nano scales for biomaterials surface functionalization.